GC-MS analysis, anti-tyrosinase, and antioxidant activities of syzygium claviflorum fruits extract - Adli, Muhammad Amirul; Abdul Halim Yap, Abdullah Haniff; Payaban, Monporn; Mohd Zohdi, Rozaini (Faculty of Pharmacy, 2025)
Excessive oxidative stress and tyrosinase activity are critical factors in the development of various dermatological issues, including hyperpigmentation and accelerated aging. Given the growing interest in natural products for their potential therapeutic benefits, this study aimed to determine the phytochemical compositions and evaluate the antioxidant and tyrosinase inhibitory activities of ethanolic fruit extracts from Syzygium claviflorum. Gas chromatography-mass spectrometry (GC-MS) was employed to analyze the phytochemical components of the extract. The tyrosinase inhibitory activity was evaluated using a mushroom tyrosinase inhibitory assay, while the antioxidant capacity of the extract was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and ferric reducing antioxidant power (FRAP) assays. GC-MS analysis revealed that phenol was the major constituent, representing 17.71% of the extract, followed by carboxylic acid at 6.69%. The extract exhibited significant anti-tyrosinase activity, with an inhibition rate of 70.64±0.22% and an IC50 value of 41.82 ± 1.43 μg/mL. Additionally, the extract demonstrated a DPPH radical scavenging activity of 55.32 ± 1.32% with an IC50 value of 212.46 ± 1.73 μg/mL and a FRAP value of 296.72 ± 1.12 μM Fe² + . These findings suggested that S. claviflorum ethanolic fruit extract demonstrated antioxidant and tyrosinase inhibitory activities, warranting further investigation for its potential applications in skincare.